Deep carbonate reservoir characterisation using multi-seismic attributes via machine learning with physical constraints. (1st November 2021) - Chen, Yuanyuan; Zhao, Luanxiao; Pan, Jianguo; Li, Chuang; Xu, Minghui; Li, Kejian; Zhang, Fengshou; Geng, Jianhua
Abstract: Seismic characterisation of deep carbonate reservoirs is of considerable interest for reservoir distribution prediction, reservoir quality evaluation and reservoir structure delineation. However, it is challenging to use the traditional methodology to predict a deep-buried carbonate reservoir because of the highly nonlinear mapping relationship between heterogeneous reservoir features and seismic responses. We propose a machine-learning-based method (random forest) with physical constraints to enhance deep carbonate reservoir prediction performance from multi-seismic attributes. We demonstrate the effectiveness of this method on a real data application in the deep carbonate reservoir of Tarim Basin, Western China. We first perform feature selection on multi-seismic attributes, then four kinds of physical constraint (continuity, boundary, spatial and category constraint) transferred from domain knowledge are imposed on the process of model building. Using the physical constraints, the F1 score of reservoir quality and reservoir type can be significantly improved and the combination of the effective physical constraints gives the best prediction of performance. We also apply the proposed strategy on 2D seismic data to predict the spatial distribution of reservoir quality and type. The seismic prediction results provide a reasonable description of the strong heterogeneity of the reservoir, offering insights into sweet spot detection and reservoir development.